Case Report: A novel WRN mutation in Werner syndrome patient with diabetic foot disease and myelodysplastic syndrome - Peng, Huifang; Wang, Jie; Liu, Yanyun; Yang, Haiping; Li, Liping; Ma, Yujin; Zhuo, Huiqin; Jiang, Hongwei (Frontiers in Endocrinology, 2022)
Werner syndrome is an autosomal recessive rare disease caused by a WRN gene mutation, which is rarely reported in the Chinese population. We report the clinical and genetic data of a Chinese patient with Werner syndrome. The proband was a 40-year-old male patient who presented with diabetic foot ulcers, accompanied by short stature, cataracts, hypogonadism, and hair thinning, and myelodysplastic syndrome (MDS) occurred after 18 months. Genetic sequencing showed there were compound heterozygous mutations as c.3384-1G>C and c.3744dupA in the WRN gene. The c.3744dupA mutation is a novel pathogenic variation for Werner syndrome.